The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5897/ajpac2014.0591
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of heavy metal ions onto chitosan grafted cocoa husk char

Abstract: The use of chitosan-grafted cocoa husk char (CCH) and unmodified cocoa husk char (CH) as adsorbents for the removal of Cr 6+ and Pb 2+ were studied. The adsorption efficiencies were compared with that of the commercial activated carbon (GAC F-300). Energy Dispersive X-ray spectroscopy (EDS) was used to determine the elemental compositions of the adsorbents while Scanning Electron Microscope (SEM) was used for the surface texture and morphological characteristics of the cocoa husk. The study optimised metal ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…It can be concluded that crosslinked chitosan-g-PMAm exhibits good adsorption capacity and can be workable for new potential adsorption systems. Polyaniline grafted crosslinked chitosan 114 (Igberase & Osifo, 2015) Iodate doped chitosan composite 22.2 (Gedam & Dongre, 2015) Chitosan modified cocoa husk carbon 263.2 (Aderonke et al, 2014) Halomonas BVR1 immobilized in chitosan 24.2 (Manasi, Rajesh, & Rajesh 2015) Bromine pretreated chitosan 1.8 (Dongre, Thakur, Ghugal, & Meshram, 2012) Crosslinked chitosan-clay beads 7.9 (Tirtom, Dincer, Becerik, Aydemir, & Çelik , 2012) Chitosan crosslinked with citric acidglutaraldehyde 103.6 (Suc & Ly, 2013) Crosslinked chitosan-g-PMAm 250…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…It can be concluded that crosslinked chitosan-g-PMAm exhibits good adsorption capacity and can be workable for new potential adsorption systems. Polyaniline grafted crosslinked chitosan 114 (Igberase & Osifo, 2015) Iodate doped chitosan composite 22.2 (Gedam & Dongre, 2015) Chitosan modified cocoa husk carbon 263.2 (Aderonke et al, 2014) Halomonas BVR1 immobilized in chitosan 24.2 (Manasi, Rajesh, & Rajesh 2015) Bromine pretreated chitosan 1.8 (Dongre, Thakur, Ghugal, & Meshram, 2012) Crosslinked chitosan-clay beads 7.9 (Tirtom, Dincer, Becerik, Aydemir, & Çelik , 2012) Chitosan crosslinked with citric acidglutaraldehyde 103.6 (Suc & Ly, 2013) Crosslinked chitosan-g-PMAm 250…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Precipitation is the most widely used method for the removal of copper as its hydroxide or sulfide. However, major problem with precipitation is the disposal of precipitated cupric hydroxide (Aderonke et al 2014). These existing methods that are generally expensive (Ferraz et al 2015) lead to incomplete metal removal, high energy consumption and generation of toxic sludge.…”
Section: Introductionmentioning
confidence: 99%
“…From Table-3, the increase in the values of the Freundlich constant (K f ), as adsorption capacities of chitosan for the metal ions, is in the order of Cu>As. The higher adsorption capacity of chitosan for Cu as compared to As may be attributed to its greater adsorption affinity toward chitosan [53].…”
Section: Adsorption Isotherm For As and Cu Ions Removal From Electroplating Wastewatermentioning
confidence: 99%